2016
DOI: 10.3390/molecules21070876
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel Benzothiazole Derivatives as Selective PI3Kβ Inhibitors

Abstract: Abstract:A novel series of PI3Kβ (Phosphatidylinositol-3-kinases beta subunit) inhibitors with the structure of benzothiazole scaffold have been designed and synthesized. All the compounds have been evaluated for inhibitory activities against PI3Kα, β, γ, δ and mTOR (Mammalian target of rapamycin). Two superior compounds have been further evaluated for the IC 50 values against PI3Ks/mTOR. The most promising compound 11 displays excellent anti-proliferative activity and selectivity in multiple cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…To explore the binding mode of ZLDI-8 (AO299/41409126) with ADAM-17 33 , molecular docking simulation studies were carried out by using the SURFLEX-DOCK module of the SYBYL 6.9 package version (Tripos International, St. Louis, MO, USA). X-ray crystal structure of ADAM-17 (PDB ID code: 2DDF) was obtained from the Protein Data Bank (PDB) ( http://www.wwpdb.org ).…”
Section: Methodsmentioning
confidence: 99%
“…To explore the binding mode of ZLDI-8 (AO299/41409126) with ADAM-17 33 , molecular docking simulation studies were carried out by using the SURFLEX-DOCK module of the SYBYL 6.9 package version (Tripos International, St. Louis, MO, USA). X-ray crystal structure of ADAM-17 (PDB ID code: 2DDF) was obtained from the Protein Data Bank (PDB) ( http://www.wwpdb.org ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the druggability predition of 6c was carried out, while using software ADMET Predictor version 9.5 (Simulations Plus Inc., Lancaster, CA, USA) [29]. The computer simulation results are listed in Table 2 and revealed that the absorption, metabolism, and toxicity properties of compound 6c were all in reasonable range, which suggested that 6c might own a reasonale druglike property.…”
Section: Druglike Property Prediction Of 6cmentioning
confidence: 99%
“…General Procedure for the Synthesis of Compounds 4a-i and 5 2 (3.87 g, 10 mmol) was heated at 195-210 • C for 30 min. under vacuum(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) to afford the deep purple solid, which was acidified with ethanol/concentrated HCl (95/5) and the yellow solution was acquired. The solvent was removed, and the residue was purified by flash chromatography while using CH 2 Cl 2 /CH 3 OH as the gradient eluent, affording the intermediate 3(3.43 g, 80%) as a brown solid.Triethylamine (1.80 mmol) was added to a stirred solution of 3 (100 mg, 0.40 mmol) in anhydrous CH 3 CN (6 mL) first, 10 min.…”
mentioning
confidence: 99%
“…mTOR is the mammalian target of rapamycin composed of 2549 amino acids with a molecular weight of 289 kDa, belonging to serine/threonine protein kinase. It widely exists in various mammalian cells and participates in many cell processes, such as cell growth, proliferation, protein synthesis, transcription and metabolism [6]. From the C-terminal to the N-terminal, mTOR is successively distributed with focal adhesion targeting domain of C-terminal, negative regulatory domain, kinase domain, FKBP12 rapamycin binding and focal adhesion targeting domain, and it belongs to phosphoinositide 3-kinase-related protein kinases (PIKKs) [7].…”
Section: Mtor and Mtor Inhibitorsmentioning
confidence: 99%
“…mTOR can form two different complexes, mTORC1 and mTORC2 by combining with different proteins. The upstream activators and downstream effectors of mTORC1 and mTORC2 are different [8], and they coordinate each other to regulate the cell cycle process [6].…”
Section: Mtor and Mtor Inhibitorsmentioning
confidence: 99%